Does Depression Influence Academic Stress Among University Students Through Anxiety? - Asriana Kibtiyah; Yusuf Ahmed Muaz; Ariga Barhordin; Khoirul Umam; Evita Widiyati; Fita Mustafida (Kuras Institute, 2026)
This study investigates how depression contributes to academic stress among university students, with anxiety functioning as a mediating factor. The research arises from growing concerns about students’ emotional challenges linked to demanding academic expectations and post-pandemic adjustment. Using a quantitative design, the study involved 76 undergraduates recruited through purposive sampling. Standardised measures of depression, anxiety, and academic stress were administered, and the data were analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM) in SmartPLS 4. The findings showed that depression significantly predicted academic stress (β = 0.352, p = .003) and strongly increased anxiety levels (β = 0.642, p < .001). Anxiety also contributed to academic stress (β = 0.380, p < .001) and served as a partial mediator between depression and academic stress (β = 0.244, p = .004). The model displayed moderate explanatory power (R² = 0.440). Overall, the results support Lazarus and Folkman’s (1984) transactional stress model and Beck’s (1979) cognitive theory, highlighting the interaction of cognitive and emotional factors. Practically, the study underscores the importance of counselling approaches that strengthen cognitive–emotional regulation and promote mental health literacy in universities.